ANALISIS PENULISAN SURAT YĀSĪN BERDASARKAN KAIDAH RASM ῾UTHMĀNĪ DALAM AL-QUR’AN KUDUS CETAKAN 1974 - Nafi'atul Ummah; Abdul Wadud Kasful Humam (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
This research highlights the divergence in writing between the 1974 Menara Kudus Quranic printing and the standardized Uthmānīc style in sura Yāsīn. Having examined literatures related to the history of the Kudus version including the text itself, this research concludes that the formerdoes not follow the later in three cases: the omitting (á¸¥adhf) of the alif and the skeleton of the alone hamzahas well as the connected two hamzah at the beginning of a sentence. Keyword: Sura Yāsīn, rasm Quran Kudus 1974, Uthmnic style.